Ontological Reduction - Grossmann, Reinhardt (Indiana University Press, 1973)
Ontological Reduction offers a philosophical analysis, described in its author's 1970 preface to the text as follows: "A discussion of ontological reduction, with special reference to the status of selected categories and culminating in the outline of a list of categories."